STUDENTS' SAVING BEHAVIOUR: WHAT ARE THE MOTIVES THAT INFLUENCE THEM TO SAVE? - Hartono, Ulil; Isbanah, Yuyun (Fakultas Ekonomi dan Bisnis, UNTAN, 2022)
This study aims to determine the determinants of saving behavior using financial literacy as a mediating variable. The endogenous variable in this study was saving behavior, while the exogenous variables were financial literacy, parental socialization, peer influence, and self-control. The respondents were 300 students from the Faculty of Economics of Indonesia. Data were analyzed by Structural Equation Modelling (SEM) using STATA software. The results show that parental socialization and peer influence positively affect financial literacy, whereas self-control does not. Financial literacy directly affects saving behavior. Parental socialization and peer influence directly influence saving behavior. The results provide a new understanding of the importance of financial literacy in encouraging student-saving behavior. The role of parents and peers in the environment is essential for improving students